2015
DOI: 10.1021/acs.iecr.5b02717
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oil Recovery Using Micron-Size Polyacrylamide Elastic Microspheres: Underlying Mechanisms and Displacement Experiments

Abstract: Micron-size polyacrylamide elastic microsphere (MPEM) is a newly developed profile control and oil displacement agent for enhanced oil recovery in heterogeneous reservoirs.In this study, laboratory experiments were performed to characterize the viscoelastic properties of MPEMs in brine water. A transparent sandpack micromodel was used to observe the microscopic flow and displacement mechanisms, and parallel-sandpack models were used to investigate the profile control and oil displacement performance using MPEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…Most of the literature suggests a representative shear rate of 7.3 s -1 for laboratory studies, as it is the typical reservoir shear rate [23]. It is well understood that the enhanced viscosity can increase the macroscopic displacement efficiency [37]. Recent studies have also found that the elasticity of a polymer can help in recovering residual trapped oil [38,39].…”
Section: Rheologymentioning
confidence: 99%
“…Most of the literature suggests a representative shear rate of 7.3 s -1 for laboratory studies, as it is the typical reservoir shear rate [23]. It is well understood that the enhanced viscosity can increase the macroscopic displacement efficiency [37]. Recent studies have also found that the elasticity of a polymer can help in recovering residual trapped oil [38,39].…”
Section: Rheologymentioning
confidence: 99%
“…This high water cut in production wells has become a common problem in high temperature and high salinity oilfield developments [6][7][8]. Conformance control is widely used and has been proven to be an important measure to improve the efficiency of water flooding and enhance the oil recovery [9][10][11][12][13][14]. However, the lack of a suitable conformance control agent restricts the popularization and application of conformance control treatment in high temperature and high salinity reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…They can be synthesized for crosslinked hydrophilic microspheres with excellent three‐dimensional networks and good flexibility which are valuable in oil development. There are some recent studies that have conducted pure polymer microspheres on the plugging properties of oil field depth profile control agents and their flow diversion effects . However, these pure organic hydrophilic polymers always show excessive swelling degree, low spherical degree, and weak shear resistance which are not beneficial for practical applications .…”
Section: Introductionmentioning
confidence: 99%
“…There are some recent studies that have conducted pure polymer microspheres on the plugging properties of oil field depth profile control agents and their flow diversion effects. 24,25 However, these pure organic hydrophilic polymers always show excessive swelling degree, low spherical degree, and weak shear resistance which are not beneficial for practical applications. 26 Moreover, the low dispersion of pure polymer microspheres also restricts their injection and migration in reservoir channels.…”
Section: Introductionmentioning
confidence: 99%